2021
DOI: 10.1159/000511467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Long-Term Corticosteroid Monotherapy in 26 Cases of Nephrotic Syndrome with Biopsy-Proven Membranous Nephropathy Induced by Seronegative Hepatitis B Virus-Associated Glomerulonephritis

Abstract: <b><i>Background:</i></b> Hepatitis B virus-associated glomerulonephritis (HBV-GN) can occur in patients with negative HBV serological antigens. Little is known about the treatment of seronegative HBV-GN (sn HBV-GN). The aim of this prospective study was to evaluate the efficacy and safety of corticosteroids in the treatment of sn HBV-GN. <b><i>Methods:</i></b> Twenty-six patients with nephrotic syndrome induced by seronegative HBV-associated membranous nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ochi et al reported a patient with HBV-MN treated with oral corticosteroids and cyclosporine combined with entecavir who achieved complete remission ( 19 ). In addition, patients negative for HBV-DNA treated with corticosteroid monotherapy showed a relatively high response without HBV reactivation ( 20 ). However, further studies are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Ochi et al reported a patient with HBV-MN treated with oral corticosteroids and cyclosporine combined with entecavir who achieved complete remission ( 19 ). In addition, patients negative for HBV-DNA treated with corticosteroid monotherapy showed a relatively high response without HBV reactivation ( 20 ). However, further studies are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%